Exfoliation-induced nanoribbon formation of poly(3,4-ethylene dioxythiophene) PEDOT between MoS2 layers as cathode material for lithium batteries - Murugan, A. Vadivel; Quintin, M.; Delville, M. H.; Campet, Guy; Gopinath, Chinnakonda S.; Vijayamohanan, K. (Journal of Power Sources, 2006)
A new type of layered nanocomposite synthesized by delaminated MoS2 nanosheets and poly(3,4-ethylenedioxythiophene) (PEDOT) are restacked to produce alternate polymer nanoribbons between layers Of MoS2 with an interlayer distance of similar to 1.38 nm. The unique properties of resulting nanocomposite are investigated by powder XRD, XPS, SEM, TEM, and four-probe conductivity measurements. The obtained nanocomposite can be used as a cathode material for a small power rechargeable lithium battery as demonstrated by the electrochemical insertion of lithium into the PEDOT/MoS2 nanocomposite. A significant enhancement in the discharge capacity (100 mAh g(-1)) is observed compared with that (40 mAh g(-1)) for MoS2. (c) 2005 Elsevier B.V All rights reserved.
Keywords: cathode material; lithium batteries; MoS2; organic-inorganic nanocomposite; PEDOT-nanoribbons

Effect of method of preparation on hydrodesulphurization activity of Co- or Ni-promoted MoS2/SBA-15 catalysts - Garg, Shelu; Soni, Kapil; Prasad, V. V. D. N.; Kumar, Manoj; Bhaskar, Thallada; Gupta, J. K.; Dhar, G. Murali; Gopinath, Chinnakonda S. (Journal of Chemical Sciences, 2014)
Ordered mesoporous material SBA-15 was synthesized and used as a support for the preparation of molybdenum sulphide catalysts through precipitation from homogeneous solution (PFHS) technique with the Mo content varying from 2-12 wt%. The prepared catalysts were evaluated for thiophene hydrodesulphurizadon catalytic activities at 400 degrees C. Catalysts prepared through PFHS method resulted in highly dispersed MoS2 catalysts, which were inferred from powder X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), low temperature oxygen chemisorptions (LTOC) and BET surface area analysis. The relationship between XPS intensity ratio, oxygen chemisorption and catalytic activities is discussed in terms of highly dispersed nano particles of MoS2 and its consequence in accommodating more promoted atoms at the edge sites.
21st National Symposium on Catalysis (CATSYMP), CSIR Indian Inst Chem Technol, Hyderabad, INDIA, FEB 11-13, 2013
Keywords: HDS; MoS2; PFHS method; promotional effects; SBA-15

MoS2 nanoparticles and h-BN nanosheets from direct exfoliation of bulk powder: one-step synthesis method - Thripuranthaka, M.; Rout, Chandra Sekhar; Late, Dattatray J. (Materials Research Express, 2014)
We report facile synthesis of MoS2 nanoparticles and h-BN nanosheets using ultrasonication method in suitable solvents such as N-Methyl-2-pyrrolidone and ethylene glycol, respectively. The average size of MoS2 nanoparticles observed from TEM analysis were 4-5 nm and about a few hundreds of nm for h-BN nanosheets. Raman spectroscopy carried out on nanoparticle samples confirms the formation of MoS2 nanoparticles and h-BN nanosheets. UV-vis absorption and photoluminescence (PL) measurements carried out on the products show typical absorption and luminescence spectra of MoS2 and h-BN. Further, we attempted to decorate gold nanoparticles on nanosheets of MoS2 and h-BN which show subsequent change in Raman spectra due to charge transfer interaction.
Keywords: h-BN; MoS2; Nanoparticles; nanosheets; Optical properties

Pulsed laser-deposited MoS2 thin films on W and Si: field emission and photoresponse studies - Late, Dattatray J.; Shaikh, Parvez A.; Khare, Ruchita T.; Kashid, Ranjit V.; Chaudhary, Minakshi V.; More, Mahendra A.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2014)
We report field electron emission investigations on pulsed laser-deposited molybdenum disulfide (MoS2) thin films on W-tip and Si substrates. In both cases, under the chosen growth conditions, the dry process of pulsed laser deposition (PLD) is seen to render a dense nanostructured morphology of MoS2, which is important for local electric field enhancement in field emission application. In the case of the MoS2 film on silicon (Si), the turn-on field required to draw an emission current density of 10 mu A/cm(2) is found to be 2.8 V/mu m. Interestingly, the MoS2 film on a tungsten (W) tip emitter delivers a large emission current density of similar to 30 mA/cm(2) at a relatively lower applied voltage of similar to 3.8 kV. Thus, the PLD-MoS2 can be utilized for various field emission-based applications. We also report our results of photodiode-like behavior in (n- and p- type) Si/PLDMoS2 heterostructures. Finally we show that MoS2 films deposited on flexible kapton substrate show a good photoresponse and recovery. Our investigations thus hold great promise for the development of PLD MoS2 films in application domains such as field emitters and heterostructures for novel nanoelectronic devices.
Keywords: field emission; MoS2; photodiode heterostructures; pulsed laser deposition; thin film

Stable field emission from layered MoS2 nanosheets in high vacuum and observation of 1/f noise - Kashid, Ranjit V.; Joag, Pracheetee D.; Thripuranthaka, M.; Rout, Chandra S.; Late, Dattatray J.; More, Mahendra A. (Nanomaterials and Nanotechnology, 2015)
Field emission and current noise of hydrothermally synthesized MoS2 nanosheets are investigated in ultra-high-vacuum and industrially suited high-vacuum conditions. The study reveals that the emission turn-on field is pressure dependent. Moreover, the MoS2 nanosheets exhibit more stable field-electron emission in high-vacuum than in ultra-high-vacuum conditions. The investigations on field-emission current fluctuations show features of 1/f-type noise in ultra-high-vacuum and high-vacuum conditions, attributed to adsorption and desorption processes. The post-field-emission results indicate the MoS2 nanosheets are a robust field emitter in high-vacuum conditions.
Keywords: Electron emission; layered materials; MoS2; Noise measurement; Raman spectroscopy

Facile synthesis and electrochemical evaluation of PANI/CNT/MoS2 ternary composite as an electrode material for high performance supercapacitor - Thakur, A.K.; Deshmukh, A. B.; Choudhary, R. B.; Karbhal, I.; Majumder, M.; Shelke, M.V. (Materials Science and Engineering B: Solid-State Materials for Advanced Technology, 2017)
Synthesis of a novel ternary composite consisting of polyaniline (PANI), functionalized multi-walled carbon nanotubes (CNTs) and molybdenum disulfide (MoS2), via an in-situ polymerization method is reported. Detailed structural and electrochemical characterization shows that incorporation of a small amount of MoS2 in PANI/CNT composite tends to eliminate agglomeration problem of CNT. The PANI/CNT/MoS2 ternary composite reaches a specific capacitance of 350 F/g at the current density 1 A/g corresponding to a 5% MoS2 content. This ternary composite shows good cycling stability even at a higher energy density of 10 A/g. Further, PANI/CNT/MoS2 composite electrode shows higher energy density (7.77 Wh/kg) and power density (2140 W/kg) as compared to PANI/CNT composite without MoS2.
Keywords: MoS2; polyaniline; supercapacitor; Ternary Composite